The role of electronic medical records in improving the quality of health care services: Comparative study. (July 2019) - Ayaad, Omar; Alloubani, Aladeen; ALhajaa, Eyad Abu; Farhan, Mohammad; Abuseif, Sami; Al Hroub, Ahmad; Akhu-Zaheya, Laila
Highlights: Encourages others to look at the effect of implementation of EHR's in their Country. Identify the quality of health care services' differences between adopted Electronic Medical Record (EMR) and paper-based record hospitals. Identify how the quality of electronic medical records affect the quality of health care services. The research recommends increasing the awareness about domains and function of EMR and its role in improving the quality of health service. The gaps between the perception and expectation of quality of health service are lower in the EMR adopted hospital. Abstract: Purpose: The purpose of this study is to identify the quality of health care services' differences between adopted Electronic Medical Record (EMR) and paper-based record hospitals. Moreover, to identify how the quality of electronic medical records affect the quality of health care services. Methods: A cross-sectional, descriptive, and comparative design was utilized between two groups in this study. The study was conducted in two public hospitals in Jordan. One hospital which had adopted the EMR system in their works and another hospital that had paper-based record. A convenience sampling technique was used to select 410 health professionals from the selected hospitals (205 participants from each hospital). SERVQUAL and E-S-QUAL questionnaires were adopted to collect the data about the quality of EMR and quality of health care service. Statistical Package for the Social Sciences (SPSS) Version 21 was deployed to analyze the collected data. Result: The results indicate that the quality of health care services (expectation and perception) in EMRs adopted hospital is higher than the quality of health care services in the hospital using paper-based record. Quality of EMRs and its domains (efficiency, availability, fulfilment, and privacy) are high in both perception and expectation of health care professionals in EMR-adopted hospitals. Moreover, there is a significant relationship between the whole perception of the quality of electronic medical records and the quality of services, and between each domain of quality of EMRs and total perception of quality of services. Conclusion: Adoption of a high quality of EMR has a significant impact on improving the quality of health care services.